The West without water : what past floods, droughts, and other climatic clues tell us about tomorrow - Ingram, B. Lynn, 1961-; Malamud-Roam, Frances, 1961- (University of California Press, 2013)
The West without Water documents the tumultuous climate of the American West over twenty millennia, with tales of past droughts and deluges and predictions about the impacts of future climate change on water resources. Looking at the region's current water crisis from the perspective of its climate history, the authors ask the central question of what is "normal" climate for the West, and whether the relatively benign climate of the past century will continue into the future. The West without Water merges climate and paleoclimate research from a wide variety of sources as it intro.